MEK1/2 Inhibition Synergistically Enhances the Preventive Effects of Normobaric Oxygen on Spinal Cord Injury in Decompression Sickness Rats - Zhou, Quan; Meng, Xiangyang; Huang, Guoyang; Yi, Hongjie; Zheng, Juan; Zhang, Kun; Xu, Weigang (Frontiers in Physiology, 2021)
A previous study from our team found that hyperbaric oxygen (HBO) pretreatment attenuated decompression sickness (DCS) spinal cord injury by upregulating heat shock protein 32 (HSP32) via the ROS/p38 MAPK pathway. Meanwhile, a MEK1/2-negative regulatory pathway was also activated to inhibit HSP32 overexpression. The purpose of this study was to determine if normobaric oxygen (NBO) might effectively induce HSP32 while concurrently inhibiting MEK1/2 and to observe any protective effects on spinal cord injury in DCS rats. The expression of HSP32 in spinal cord tissue was measured at 6, 12, 18, and 24 h following NBO and MEK1/2 inhibitor U0126 pretreatment. The peak time of HSP32 was observed at 12 h after simulated air diving. Subsequently, signs of DCS, hindlimb motor function, and spinal cord and serum injury biomarkers were recorded. NBO-U0126 pretreatment significantly decreased the incidence of DCS, improved motor function, and attenuated oxidative stress, inflammatory response, and apoptosis in both the spinal cord and serum. These results suggest that pretreatment with NBO and U0126 combined can effectively alleviate DCS spinal cord injury in rats by upregulating HSP32. This may lead to a more convenient approach for DCS injury control, using non-pressurized NBO instead of HBO.